Combined effects of shade and drought on physiology, growth, and yield of mature cocoa trees - Mensah, E.O.; Raebild, A.; Asare, R.; Amoatey, C.; Markussen, B.O.; Owusu, K.; Asitoakor, B.K.; Vaast, Philippe (Elsevier, 2023)
Climate models predict decreasing precipitation and increasing air temperature, causing concern for the future of cocoa in the major producing regions worldwide. It has been suggested that shade could alleviate stress by reducing radiation intensity and conserving soil moisture, but few on-farm cocoa studies are testing this hypothesis. Here, for 33 months, we subjected twelve-year cocoa plants in Ghana to three levels of rainwater suppression (full rainwater, 1/3 rainwater suppression and 2/3 rainwater suppression) under full sun or 40 % uniform shade in a split plot design, monitoring soil moisture, physiological parameters, growth, and yield. Volumetric soil moisture (ϴw) contents in the treatments ranged between 0.20 and 0.45 m3m−3 and increased under shade. Rainwater suppression decreased leaf water potentials (ѱw), reaching −1.5 MPa in full sun conditions indicating severe drought. Stomatal conductance (gs) was decreased under the full sun but was not affected by rainwater suppression, illustrating the limited control of water loss in cocoa plants. Although pre-dawn chlorophyll fluorescence (Fv/Fm) indicated photoinhibition, rates of photosynthesis (Pn) were highest in full sun. On the other hand, litter fall was highest in the full sun and under water stress, while diameter growth and carbon accumulation increased in the shade but was negatively affected by rainwater suppression. Abortion of fruits and damage to pods were high under shade, but dry bean yield was higher compared to under the full sun. The absence of interactions between shade treatments and rainwater suppression suggests that shade may improve the performance of cocoa, but not sufficiently to counteract the negative effects of water stress under field conditions.